Height and Prostate Cancer Risk: A Large Nested Case-Control Study (ProtecT) and Meta-analysis - Zuccolo, Luisa (2008)
BACKGROUND: Height, a marker of childhood environmental exposures, is positively associated with prostate cancer risk, perhaps through the insulin-like growth factor system. We investigated the relationship of prostate cancer with height and its components (leg and trunk length) in a nested case-control study and with height in a dose-response meta-analysis. METHODS: We nested a case-control study within a population-based randomized controlled trial evaluating treatments for localized prostate cancer in British men ages 50 to 69 years, including 1,357 cases detected through prostate-specific antigen testing and 7,990 controls (matched on age, general practice, assessment date). Nine bibliographic databases were searched systematically for studies on the height-prostate cancer association that were pooled in a meta-analysis. RESULTS: Based on the nested case-control, the odds ratio (OR) of prostate-specific antigen-detected prostate cancer per 10 cm increase in height was 1.06 [95% confidence interval (95% CI): 0.97-1.16; p(trend) = 0.2]. There was stronger evidence of an association of height with high-grade prostate cancer (OR: 1.23; 95% CI: 1.06-1.43), mainly due to the leg component, but not with low-grade disease (OR: 0.99; 95% CI: 0.90-1.10). In general, associations with leg or trunk length were similar. A meta-analysis of 58 studies found evidence that height is positively associated with prostate cancer (random-effects OR per 10 cm: 1.06; 95% CI: 1.03-1.09), with a stronger effect for prospective studies of more advanced/aggressive cancers (random-effects OR: 1.12; 95% CI: 1.05-1.19). CONCLUSION: These data indicate a limited role for childhood environmental exposures—as indexed by adult height—on prostate cancer incidence, while suggesting a greater role for progression, through mechanisms requiring further investigation.